Tailored Additives for Incorporation of Antibacterial Functionality Into Laser Sintered Parts - Wingham, James R.; Ahmed , Ifty; Islam , Md Towhidul; Shepherd , Joanna; Majewski , Candice (Frontiers in Biomaterials Science, 2022)
Infectious disease is a major cause of death worldwide, and novel methods capable of controlling the spread of disease are in high demand. This research presents a method of producing antimicrobial microcomposites by exploiting the powder-based nature of the Laser Sintering Additive Manufacturing process, via the incorporation of silver-containing additives. Silver phosphate glass additives in different formulations were designed to determine the effect of dissolution rate on the antimicrobial efficacy. These were characterised and successfully incorporated into polyamide 12 parts, without affecting the mechanical properties. The printed microcomposite parts displayed both bactericidal and antibiofouling effects against Gram-positive and Gram-negative bacteria in nutrient-poor conditions, with the efficacy found to be more sensitive to silver content than degradation rate.